Synthesis and Properties of α-Bromomethyl-Substituted β-Ethoxyvinyl Polyfluoroalkyl Ketones - Bugera, Maksym Ya.; Tarasenko, Karen V.; Kukhar, Valery P.; Röschenthaler, Gerd-Volker; Gerus, Igor I. (Synthesis, 2013)
An efficient and practical method for the synthesis of α-bromomethyl-substituted β-alkoxyvinyl polyfluoroalkyl ketones is reported. These highly functionalized α-bromomethyl enones easily react with various nucleophiles and binucleophiles affording a wide variety of new functionalized enones and heterocyclic systems that are perspective starting materials for the synthesis of compounds with potentially high biological and pharmacological activity.
Keywords: enones; fluorine; halogenation; radical reaction; nucleophilic reaction; heterocycles